THE APPLICATION OF CRITICAL READING IN READING LOGS ASSIGNMENT AS PERCEIVED BY FRESHMEN OF THE FAST-TRACK DIVISION, FELTE, ULIS, VNU = NGHIÊN CỨU VỀ VIỆC ÁP DỤNG KỸ NĂNG ĐỌC PHÊ PHÁN KHI LÀM READING LOGS CỦA SINH VIÊN NĂM NHẤT HỆ CHẤT LƯỢNG CAO, KHOA SƯ PHẠM TIẾNG ANH, TRƯỜNG ĐẠI HỌC NGOẠI NGỮ, ĐẠI HỌC QUỐC GIA HÀ NỘI - Nguyễn, Phương Liên (2020)
Infobesity – Information obesity, which means information overload, reflects exactly what people are experiencing in this era of technologies. With technological advancements, people become indecisive when reading different writings written by different people with different viewpoints but about the same issue. Gradually, people’s critical mind gets eroded with the words they read. Being aware of the information trap, it is of the utmost importance for freshmen in the Fast-track program of Faculty of English Language Teacher Education (FELTE) – University of Languages and International Studies (ULIS) to avoid being baited by developing critical reading proficiency.